Anonymous authentication scheme based on one-off public key in pervasive computing environments - Chang-yuan LUO; Shi-wei HUO; Hong-zhi XING (Tongxin xuebao)
A signature scheme with the one-off public key was proposed based on identity-based cryptography,which had less calculating and communicating expense compared with available schemes.An anonymous authentication scheme was designed based on the proposed signature scheme.When users committed,service provider together with the trusted center could reveal the malicious user's identity.The proposed scheme can realize strong anonymity and prevent the user committing.